Nanobubbles and nanoparticles. (October 2021) - Alheshibri, Muidh; Al Baroot, Abbad; Shui, Lingling; Zhang, Minmin
Abstract: Gas saturated solutions have attracted great attention in the past two decades with reports of stable nanobubbles in solutions. The fundamental interest focus arises from the surprising stability which opens up a wide range of potential applications where the interactions between particles and nanobubbles are important. Here, we review the current state of knowledge on systems involving both nanobubbles and nanoparticles. As nanoparticles and nanobubbles are found together in many circumstances, particularly those involving applications of nanobubbles, knowledge of these systems is important. This includes examining the formation of nanoparticles from nanobubbles, the nucleation of nanobubbles from nanoparticles, and the interactions between nanobubbles and nanoparticles. It is clear that further work is required to more fully understand these systems, in particular on the problem of nanobubble nucleation and nanobubble–nanoparticle interactions at the submicron scale.